Separation of atomic-scale spin contrast on NiO(0 0 1) by magnetic resonance force microscopy. (1st September 2017) - Arima, Eiji; Naitoh, Yoshitaka; Li, Yan Jun; Sugawara, Yasuhiro
Abstract: In magnetic exchange force microscopy, images contain the topographic contrast mixed with the spin contrast on the sample surface. In this study, we propose a new method of magnetic resonance force microscopy using ferromagnetic resonance to extract only the spin contrast. In this method, the magnetization of a magnetic cantilever is modulated by ferromagnetic resonance to separate the spin contrast and topographic contrast. We succeeded in obtaining a spin image of Ni atoms on a NiO (0 0 1) surface. Furthermore, we successfully detected the superexchange interaction between the tip apex atom and the second layer of Ni atoms.